Hanseniaspora nectarophila sp nov., a yeast species isolated from ephemeral flowers - Cadez, Neza; Pagnocca, Fernando C. [UNESP]; Raspor, Peter; Rosa, Carlos A. (Soc General Microbiology, 2014)
Seven apiculate yeast strains that were isolated from the flowers of Syphocampylus corymbiferus Pohl in Brazil are genetically, morphologically and phenotypically distinct from recognized species of the genera Hanseniaspora and Kloeckera. Genetic discontinuities between the novel strains and their closest relatives were found using a networking approach based on the concatenated sequences of the rRNA gene (internal transcribed spacer and D1/D2 of the LSU), and the protein-coding genes for actin and translation elongation factor-1 alpha. Phylogenetic analysis based on the rRNA and the actin gene placed the novel species represented by the strains in close relationship to Hanseniaspora meyeri and Hanseniaspora clermontiae. PCR fingerprinting with microsatellite primers confirmed the genetic heterogeneity of the novel species. The name Hanseniaspora nectarophila sp. nov. is proposed, with UFMG POG a.1(T) (=ZIM 2311(T)=CBS 13383(T)) as the type strain; MycoBank no. MB807210. As the current description of the genus does not allow the presence of multilateral budding, an emended diagnosis of the genus Hanseniaspora Zikes is proposed.